Catheter ablation of arrhythmias : 15 years of development: Data from the Swedish Catheter Ablation Registry - Mannewald, Christine; Platonov, Pyotr G.; Fengsrud, Espen; Höglund, Niklas; Karlsson, Lars O.; Lönnerholm, Stefan; Schwieler, Jonas; Ringborn, Michael; Landén, Rúna; Tabrizi, Fariborz; Tapanainen, Jari; Braunschweig, Frieder; et al. (European Heart Journal Open, 2025)
Aims The number of patients undergoing catheter ablation is continuously growing, and techniques are improving. However, studies reporting contemporary data on catheter ablations from large real-world populations are scarce. This study aims to report characteristics and outcomes of catheter ablation from 2006 to 2020, using a nationwide registry with virtually complete coverage. Methods and results From the Swedish Catheter Ablation Registry, patients >18 years of age undergoing catheter ablation from 2006 to 2020 were included. Periprocedural data and baseline characteristics were recorded retrospectively. A total of 61 243 procedures were included. There was an overall increase in the number of catheter ablations performed. From 2006, the number of atrial fibrillation (AF) ablations performed increased from 352 procedures in 2006 to 2609 procedures in 2020. Decreased procedural times were seen in catheter ablation of accessory pathway/Wolff-Parkinson-White syndrome, atrial tachycardia (AT), atrioventricular nodal reentry tachycardia, cavotricuspid isthmus (CTI), AF, and atrioventricular junction. Between the time periods 2006-15 and 2016-20, median procedural time in AF ablations decreased from 180 to 140 min (P < 0.001). There was a decreased trend in fluoroscopy time and median dose area product for all ablation procedures (P < 0.001). For AT, CTI, and AF, the cumulative probability of requiring a repeat ablation was significantly lower for procedures performed after January 2016 (P < 0.001). Conclusion With a yearly increase in the number of ablations performed, there was a reduction in the need for repeat ablations for AF, AT, and CTI, along with reduced procedural times and lower fluoroscopy levels.
Keywords: Arrhythmias; Atrial fibrillation; Catheter ablation